Development of graphene-conductive polymer-based electrodes for noninvasive glucose biosensor - Nur Alya Batrisya Ismail (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
Noninvasive glucose monitoring provides an alternative and convenient method for diabetic patient to monitor their glucose level in comparison to the conventional method of finger-pricking. With the aim to monitor glucose painlessly, noninvasive glucose biosensor should detect minute amount of glucose available in saliva, where glucose concentration in saliva is estimated to be ~100 times lower than the concentration of glucose in blood. The kinetics of electron transfer should be thoroughly understood to ensure noninvasive glucose biosensor possessed high selectivity towards the analyte of interest. An electrochemical biosensor based on a nanocomposite material of partially reduced graphene oxide (prGO) and poly(3,4-ethylenedioxythiophene): poly(4-styrenesulfonate) (PEDOT:PSS) with glucose oxidase (GOx) immobilized via crosslinking with glutaraldehyde on screen-printed carbon electrode (SPCE), was fabricated, and analyzed using electrochemical analyses. Cyclic voltammetry (CV) performed on the transducer layer, prGO-PEDOT:PSS/SPCE showed quasi-reversible, diffusion-controlled electron transfer characteristics, with the largest electrode effective surface area being 219.09 µm2 – three times larger than bare electrodes. Analyses with electrochemical impedance spectroscopy (EIS) showed prGO-PEDOT:PSS/SPCEs to have the lowest charge transfer resistance of 163.83 Ω compared to GO-PEDOT:PSS/SPCE (427.87 Ω), PEDOT:PSS/SPCE (14.38 kΩ), GO/SPCE (46.31 kΩ) and SPCE (13.31 kΩ), which implies that the nanocomposite material has high conductivity and suitable for transducing ions to electrons at the electrode-solution interface. To evaluate the electrodes for biosensing, GOx was used as the model enzyme. CV analyses of GOx/prGO-PEDOT:PSS/SPCEs showed high sensitivity (1752.42 µA/mM.cm2) towards glucose with limit of detection (LOD) of 0.3 mM, limit of quantification (LOQ) of 1.09 mM, and linear range between 0.1 mM to 1.0 mM. The response of the GOx/prGO-PEDOT:PSS/SPCEs-based biosensor also presents good reproducibility, stability, and negligible interfering effects from ascorbic acid, uric acid, and acetaminophen. These results suggest GOx/prGO-PEDOT:PSS/SPCEs are promising transducer for noninvasive glucose sensing.